Brugada syndrome: clinical presentation and genotype : correlation with magnetic resonance imaging parameters - Rudic, Boris; Schimpf, Rainer; Dösch, Christina; Tueluemen, Erol; Schönberg, Stefan; Borggrefe, Martin; Papavassiliu, Theano (Europace, 2016)
Aims: The purpose of the this study was to evaluate a possible genotype–phenotype correlation in BrS patients and to analyze possible associations with clinical events in affected patients. SCN5A gene encodes the alpha-subunit of the voltage-gated sodium channel NaV1.5. Its mutations are associated with a broad spectrum of hereditary arrhythmias such as long-QT syndrome, cardiac conduction diseases, and Brugada syndrome (BrS). Experimental studies have shown an interaction between SCN5A and cellular cytoskeleton, explaining its functional role in cellular integrity of heart cells. Methods and results: Cardiovascular magnetic resonance was performed on 81 consecutive genetically screened BrS patients and 30 healthy controls. Left ventricular (LV) and right ventricular (RV) volumes and dimensions were assessed and compared with respect to the genotype. Brugada syndrome patients with an SCN5A mutation (16 patients; 20%) revealed significantly larger RV volumes, along with lower RV ejection fraction, than patients without a mutation or controls, indicating a more severe phenotype in patients with a mutation. Furthermore, patients with an SCN5A mutation showed significantly more often a spontaneous type 1 BrS-electrocardiogram (ECG). In multivariate analysis, the presence of a spontaneous type 1 BrS-ECG showed the strongest association with cardiac events. Receiver-operating characteristic curve analysis indicated good predictive performance of RV end-diastolic volume, RV end-systolic, and LV cardiac output (area under the curve = 0.81, 0.81, and 0.2), with respect to the presence of an SCN5A mutation. Conclusion: Brugada syndrome patients with an SCN5A mutation reveal distinct changes in RV volumes and function when compared with those without an SCN5A mutation. Furthermore, mutation-positive patients have a higher likelihood of a spontaneous type 1 BrS-ECG, which is associated with a higher incidence of clinical events. Cardiovascular magnetic resonance may provide additional insight to distinguish between SCN5A mutation-positive and -negative BrS patients.